National Narcotic Prescription Patterns by Obstetrics & Gynecology Residents [7E]. (May 2016) - Baruch, Adam D.; Morgan, Daniel; Dalton, Vanessa K.; Swenson, Carolyn W.
Abstract : INTRODUCTION: We aimed to describe Ob/Gyn resident narcotic prescription patterns in the U.S. and assess influential factors. METHODS: An anonymous survey was distributed to Ob/Gyn residents through the residency program coordinator list-serve. Demographic information and data regarding quantity of narcotics prescribed following specific procedures were obtained. Questions also addressed personal and system-level factors influencing prescription practices. Logistic regression was used to identify factors associated with being in the top-quartile for number of narcotics prescribed. RESULTS: Among the 267 respondents, 64.8% were from university programs and 35.2% were from community-based programs. Regional distribution included: Northeast (35.6%), South (28.1%), Midwest (24.3%) and West (12.0%). The median number of narcotics prescribed following primary cesarean section was 30 (IQR 28, 40) and following laparoscopic hysterectomy was 29 (IQR 20, 30). Factors associated with increased odds of prescribing in the top quartile included training in the West (OR 3.15, 95% CI 1.05–9.45, P =.4) and agreeing/strongly agreeing with: "I prescribe postoperative narcotics in a manner to avoid getting reprimanded by attendings" (OR 2.72, 95% CI 1.20–6.15, P =.02). Factors associated with decreased odds of prescribing in the top quartile included training in a community-based program (OR 0.33, 95% CI 0.15–0.71, P =.005) and agreeing/strongly agreeing with: "I am conservative with the number of narcotics I prescribe after surgery" (OR 0.34, 95% CI 0.17–0.71, P =.004). CONCLUSION: Narcotic prescribing practices of Ob/Gyn residents vary by region, institution type, personal insight and system-level factors. We suggest a data-driven initiative to establish evidence-based guidelines for narcotic prescribing in Ob/Gyn.